Análisis de los riesgos ergonómicos y psicosociales en el área de mantenimiento de la central termoeléctrica Quevedo, en la unidad de negocios Termopichincha (celec ep) - Morante Cabezas, Jazmin Jessenia (2017)
The present study consists of an ergonomic and psychosocial risk analysis, carried out in the maintenance area of the Quevedo Thermoelectric Power Plant in the Termopichincha Business Unit (CELEC EP), with a population of 43 employees. The methodology used to identify hazards was the Colombian Technical Guide (GTC 45). This guide provided criteria to identify hazards and assess risks, with the result that they are exposed to ergonomic and psychosocial risks, the Guide for the identification of ergonomic hazards of the Center of Applied Ergonomics was used to determine in a technical way the ergonomic hazards present in each workstation, the guide is based on criteria established in international technical standards (UNE, EN and ISO) of labor ergonomics, once the ergonomic hazards were identified with this guide, they were evaluated in a qualitative way using the guide for the ergonomic risk assessment of the Applied Ergonomics Center, which consists of identifying the requirements, characteristics of the task that are easily observable according to the criteria determined in the technical standards and with this the level of risk is determined, obtaining indeterminate risk for dynamic postures and for that the OWAS method was used, which showed that there are positions with category of Risk two, indicating that they are positions with the possibility of causing damage to the musculoskeletal system. For the evaluation of psychosocial risks we used the method CoPsoQ-istas 21 (version 2) were shown to be exposed to the most unfavorable situation in two dimensions. Based on these results, proposals were made for control measures for ergonomic and psychosocial risks.